A New Measure of Intra-generational Redistribution within PAYG Pension Schemes and its Application to German Micro-data - Jonas Klos; Tim Krieger; Sven Stöwhase (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper proposes a new Index for measuring intra-generational redistribution in PAYG pension schemes. This index solely requires information on contributions and pension benefits of retirees, eliminating the involvement of the contribution side in a PAYG pension scheme. As an application, we use contribution records of new German retirees to measure intra-generational redistribution in the German statutory pension scheme and the importance of certain additional benefits.
Keywords: H55; D31; C55; 330; PAYG pension systems; intra-generational redistribution; Beveridge vs. Bismarck; index; microdata; Germany